Seven new Helicopsyche (Feropsyche) Johanson, 2002 from the Neotropical region and Nearctic Mexico (Insecta: Trichoptera: Helicopsychidae) - Johanson, Kjell A.; Malm, Tobia S. (Zootaxa, 2006)
Seven new species of Helicopsyche (Feropsyche) Johanson 2002 (Helicopsychidae) are described from Mexico (H. curvipalpia new species), Panama (H. blantoni new species, H. chiriquensis new species, H. linguata new species, and H. sanblasensis new species), and Brazil (H. paprockii new species and H. cipoensis new species) based on adult material borrowed from the National Museum of Natural History (Smithsonian Institution), Washington, D. C. and the Illinois Natural History Survey, Champaign, Illinois, USA. New records are given for H. sinuata Denning & Blickle from Mexico, and H. incisa Ross and H. woldai Johanson from Panama.